Improvement of pedagogical skills through teacher participation in professional competitions. - Muskhanova, Isita (Revista Conrado, 2022)
ABSTRACT This article analyses the impact of the contest "Teacher of the Year" to improve pedagogical skills and creativity of the participants of the contest. It has been revealed that teachers who, constantly improve their skills successfully and easily perform tasks in the competition develop their creativity and it motivates them to introduce new methods in their teaching process. The positive role of participation in the competition is noted, as it helps to develop the teacher's activity, increases his psycho-pedagogical, methodical, informational and communicative competence, provides the opportunity for a teacher to reflect in new ways of doing things, get a professional expertise and try to overcome himself. The conclusion is made, that the contest "Teacher of the Year" has a positive influence on the improvement of the pedagogical excellence of teachers and contributes to disclosing of their personal potential. Keywords: Pedagogical experience, pedagogical practice, pedagogical education, practical activity, teacher. RESUMEN Este artículo analiza el impacto del concurso “Profesor del Año” para mejorar las habilidades pedagógicas y la creatividad de los participantes del concurso. Se ha revelado que los docentes que mejoran constantemente sus habilidades realizan con éxito y facilidad tareas en la competencia desarrollan su creatividad y los motiva a introducir nuevos métodos en su proceso de enseñanza. Se destaca el papel positivo de la participación en el concurso, ya que ayuda a desarrollar la actividad del docente, aumenta su competencia psicopedagógica, metódica, informativa y comunicativa, brinda la oportunidad al docente de reflexionar sobre nuevas formas de hacer las cosas, obtener una experiencia profesional y tratar de superarse a sí mismo. Se concluye que el concurso "Profesor del Año" influye positivamente en la mejora de la excelencia pedagógica de los docentes y contribuye a la divulgación de su potencial personal. Palabras clave: Experiencia pedagógica, práctica pedagógica, educación pedagógica, actividad práctica, docente.